The Invisible, the Silenced, the Excluded: Women’s Misrepresentation in the European Constitution: Невидливото, замолченото, исклученото: Погрешно претставување на жените во Европскиот устав - Dămean, Diana; Kovačić, Marina (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Diana Dămean | Диана Дамеан Title (English): The Invisible, the Silenced, the Excluded: Women’s Misrepresentation in the European Constitution Title (Macedonian): Невидливото, замолченото, исклученото: Погрешно претставување на жените во Европскиот устав Translated by (English to Macedonian): Marina Kovačić | Марина Ковачиќ Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 37-62 Page Count: 25 Citation (English): Diana Dămean, “The Invisible, the Silenced, the Excluded: Women’s Misrepresentation in the European Constitution,” Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 37-62. Citation (Macedonian): Диана Дамеан, „Невидливото, замолченото, исклученото: Погрешно претставување на жените во Европскиот устав“, превод од англиски Марина Ковачиќ, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 37-62.